2006
DOI: 10.7205/milmed.171.11.1051
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and Illnesses among Armor Brigade Soldiers during Operational Training

Abstract: This study describes injury and illness rates and some risk factors among soldiers from an armor division during a rotation at the National Training Center (Fort Irwin, California). Soldiers from a brigade of the 1st Cavalry Division were involved in a 5-week training exercise at the National Training Center. Health care visits were systematically recorded by the unit medics. Of 4,101 men and 413 women who participated in the exercise, 504 soldiers (409 men and 95 women) sought medical care at the main support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…The authors postulate that members of the Marine Corps may demonstrate Knapik et al 41 found a 23% rate of low back injury resulting from a 5-day-road march with a 46-kg fi ghting load. Darakjy et al 26 assessed the injury rate during operational training exercises and found a similar distribution of total injury rate according to rank group with the highest injury rate in junior enlisted and lowest rate in the offi cers. 26 Another potential factor affecting the rate of low back pain in these service members is the difference in educational level, which has been shown to infl uence rates of low back pain.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The authors postulate that members of the Marine Corps may demonstrate Knapik et al 41 found a 23% rate of low back injury resulting from a 5-day-road march with a 46-kg fi ghting load. Darakjy et al 26 assessed the injury rate during operational training exercises and found a similar distribution of total injury rate according to rank group with the highest injury rate in junior enlisted and lowest rate in the offi cers. 26 Another potential factor affecting the rate of low back pain in these service members is the difference in educational level, which has been shown to infl uence rates of low back pain.…”
Section: Discussionmentioning
confidence: 94%
“…Darakjy et al 26 assessed the injury rate during operational training exercises and found a similar distribution of total injury rate according to rank group with the highest injury rate in junior enlisted and lowest rate in the offi cers. 26 Another potential factor affecting the rate of low back pain in these service members is the difference in educational level, which has been shown to infl uence rates of low back pain. 29 A prerequisite of becoming an offi cer is obtaining a higher educational level, whereas enlisted service members are only required to have a high-school diploma or graduate equivalency factors are associated with the development of low back pain.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Soldiers of lower rank are more likely to perform the physical tasks that put them at higher injury risk (eg, general section rifleman duties). Those of older age and higher rank are more likely to be in staff or supervisory positions, and therefore less exposed to the physical hazards that put them at risk of injury 7 29…”
Section: Discussionmentioning
confidence: 99%
“…Known preventive measures include comfortable footwear, which includes correct sizing of boots, insoles and quality of socks 11. Assigning running shoes based on plantar shape has little influence on injury even after controlling for other injury risk factors;12–14 education and medical surveillance is required to help improve known foot problems and double pack straps help by distributing weight 15. Treatment includes education and preventative hygiene measures as well as antiperspirants 5.…”
Section: Introductionmentioning
confidence: 99%